Big Mac : the unauthorized story of McDonald's - Boas, Max; Chain, Steve (New Jersey : New American Library, 1976)
Chronicles the rise and expansion of the nation's number- one fast-food chain and the Horatio Alger life of founder Ray Albert Kroc.
This is an authorized reprint of a hardcover edition published by E.P. Dutton and Company, Inc.
Keywords: Kroc, Ray, -- 1902-1984.; McDonald's Corporation; Food supply